Distribution and prevalence of T. bryosalmonae in Austria: A first survey of trout from rivers with a shrinking population. Issue 10 (19th July 2018) - Lewisch, Eva; Unfer, Guenther; Pinter, Kurt; Bechter, Thomas; El‐Matbouli, Mansour
Abstract: The first evidence of proliferative kidney disease (PKD) in an Austrian river (the River Kamp) was documented in 2016, and no information on the PKD infection status of trout in other rivers was available. Since then, brown trout ( Salmo trutta fario ) and rainbow trout ( Oncorhynchus mykiss ) have been collected from rivers in Upper and Lower Austria for different diagnostic purposes. In this study, we summarize the recent findings of a first survey concerning the distribution of Tetracapsuloides bryosalmonae, the causative agent of proliferative kidney disease (PKD), from these samples. Between September 2015 and October 2017, a total of 280 brown trout and 39 rainbow trout were collected from 21 rivers in the provinces of Upper and Lower Austria. T. bryosalmonae was detected by PCR of kidney tissue in 17 of 21 sampled rivers and in 138 of 280 brown trout as well as in 11 of 39 rainbow trout. Pathological signs of PKD (e.g., hypertrophy of the kidney) were observed in 33 analysed brown trout and six rainbow trout samples. No correlations between fish infected by T .  bryosalmonae and the parameters size and age class, condition factor, geological origin of the streams and distribution within the river course were found, while positively tested fish are significantly increased at sampling sites exceeding water temperatures of 15°C for median periods of 115 days. The prevalence within the affected streams or stream sections is highly variable, and in single rivers, infection rates of up to 90% are confirmed.